2022
DOI: 10.3233/bmr-210055
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of the McKenzie method and spiral stabilization in patients with low back pain: A prospective, randomized clinical trial

Abstract: BACKGROUND: Low back pain (LBP) causes disability in daily life, and presents not only a health but also a socio-economic problem. New treatment options need to be tested and confirmed. OBJECTIVE: Compare the effect of the McKenzie method and spiral stabilization in patients with LBP. METHODS: Sixty patients with an average age of 47 years, which were included in our prospective, comparative study were randomly divided into two 30-member groups. One group exercised according to the McKenzie method (MDT), the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A recent study showed that these two treatment methods both have a comparable effect on improving physical function. Therefore, both are equally effective in patients with NSLBP [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study showed that these two treatment methods both have a comparable effect on improving physical function. Therefore, both are equally effective in patients with NSLBP [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Pilates [ 15 , 23 ], the McKenzie method [ 24 ], and physical therapy [ 25 ] were also investigated as the protentional interventions to improve NSLBP. Pilates is a specific type of exercise therapy used to treat NSLBP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation